Perlindungan Hukum Bagi Nasabah yang Mengalami Kerugian dalam Transaksi Perbankan Melalui Internet - Wafiya Wafiya (Kanun Jurnal Ilmu Hukum, 2012)
ABSTRACT: The emergence of internet technology has adopted by banks to create the internet banking services. Actually, banks realized that internet banking is hazardous, but banks considered internet banking as challenges and opportunities to improve their business. Bank Indonesia as banking regulator overseer created many regulations, include regulations related with regulation internet banking operation. The regulation aim to give the rule for banks, so banks do their business based on prudential banking and good corporate governance. A good business of banks, directly or indirectly, will establish the consumer protection. Unfortunatelly, if we evaluate more detail about the operation internet banking, we can find many factors that disservice to many innocent consumers, such as terms and conditions clauses that only created in banking perspective. According to consumer protection law, consumer rights should be established by banks. Law Protection Towards Consumers Having Loss Through Internet Banking Transaction